Stroke Related Knowledge, Prevention Practices and Associated Factors Among Hypertensive Patients at University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia, 2021 - Woldetsadik, Fkrte Kebede; Kassa, Tesfa; Bilchut, Workagegnehu Hailu; Kibret, Alemu kassaw; Guadie, Yisak Girma; Eriku, Getachew Azeze (Frontiers in Neurology, 2022)
Introduction Stroke is a global health problem, causing significant morbidities and mortalities in both developing and developed countries. Patients living with chronic diseases like hypertension are at a high risk of stroke. Approximately 80% of strokes could be prevented with necessary preventive practices. However, evidence in this regard is scarce in Ethiopia, particularly in the study area. Therefore, this study aimed to assess knowledge and prevention practices related to stroke among hypertensive patients at the University of Gondar comprehensive specialized hospital, northwest Ethiopia. Methods: An institution-based cross-sectional study was conducted among 393 hypertensive patients at the University of Gondar Comprehensive Specialized Hospital from May 1st to June 30th, 2021. The study participants were selected by a systematic random sampling technique. A semi-structured, interviewer-administered, and pre-tested questionnaire was used to collect data. The data was entered into EPI Info version 7.2.1 and analyzed with SPSS version 23.0. Binary logistic regression analyses were undertaken to identify associated factors. The level of significance was determined using the adjusted odds ratio (AOR) with its 95% CI at a p-value of 0.05. Results: Participants in this study had adequate knowledge of stroke and good prevention practices in 40.7% (95% CI: 35.9, 45.5) and 51.7% (95 CI: 46.8, 56.5) of cases, respectively. Attending secondary education and above 4.6 (95% CI: 2.08, 10.17), knowing someone who has had a stroke 13.17 (95% CI: 7.3, 23.77), and physical activity 4.05 (95% CI: 2.23, 7.36) were all significantly associated with adequate stroke knowledge. Furthermore, Educational status (attending primary education 2.61 (95% CI: 1.44, 4.73) and secondary education and above 3.75 (95% CI: 1.99, 7.05), being an urban dweller 9.65 (95% CI: 5.04, 18.44), duration of hypertension 1.9 (95% CI: 1.15, 3.14), knowing someone with a stroke 2.27 (95% CI: 1.30, 3.93), and physical activity 1.76 (95% CI: 1.03, 3.01) Conclusion: The proportion of participants with good ¬- related knowledge and prevention practice is low.